PENERAPAN STRATEGI PEMECAHAN MASALAH MELALUI BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII8 SMP NEGERI 8 PEKANBARU - Dewi, Ratna Sari; Roza, Yenita; Hutapea, Nahor Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Absract : This classroom action research is aimed to improve learning process and mathematics learning outcomes by implementing Problem Solving Strategy in Problem Based Learning. The research subjects are 40 heterogeneous academic ability level students of the VII8 class of Junior High School 8 Pekanbaru in academic year of 2015/2016. This research implemented in two cycles in which each cycle consisted of four phases, i.e: namely planning, implementing, observing and reflecting. By the end of each cycle, formative test was given. The data was collected by doing observation of teachers and students activities and formative test. The research shows learning process improvement after the implementation Problem Solving Strategy in Problem Based Learning.  Most of student participated actively and responsible in the learning process like discussing, presenting, responding and drawing the lesson conclusion. The member of students passing the Minimum Completeness Criteria (KKM) on base score, formative tes I (first cycle), formative test II (second cycle) were respectively 37,5%, 67,5% and 85%. The persentage of KKM achievement also indicates the increase after the implementation , this it can be said that the students learning outcomes also increase. The results of this research indicate that the implementation of Problem Solving Strategy in Problem Based Learning can improve the learning process and improve mathematics learning outcomes of VII8 class students at state junior high school 8 Pekanbaru in the academic year 2015/2016.